(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The evolution of cloud computing has ushered in the era of next-generation cloud ecosystems, characterized by the integration of multi-cloud and hybrid cloud strategies to meet diverse enterprise demands for flexibility, scalability, and resilience. Multi-cloud refers to the use of multiple public cloud services simultaneously, while hybrid cloud combines private cloud infrastructure with public cloud resources, enabling organizations to optimize workload placement, cost-efficiency, and regulatory compliance. This paper investigates the architectural design, management challenges, and performance implications of adopting multi-cloud and hybrid cloud paradigms within modern cloud ecosystems. We propose a unified framework that facilitates seamless workload orchestration, interoperability, and security across heterogeneous cloud environments. The research methodology includes a systematic literature review, simulation-based evaluation, and case studies of real-world deployments. Key performance metrics such as latency, throughput, cost, and fault tolerance are analyzed under various workload scenarios. Results demonstrate that hybrid and multi-cloud strategies provide enhanced flexibility and disaster recovery capabilities, while also introducing complexities in data governance and interoperability. Our proposed framework leverages containerization, service mesh architectures, and AI-driven orchestration to mitigate these challenges, achieving optimized resource utilization and improved application availability. Security considerations, including data encryption, identity management, and compliance with regulatory standards, are also addressed. The study concludes that next-generation cloud ecosystems require robust management frameworks to fully harness the benefits of multi-cloud and hybrid cloud adoption. Future work will explore advancements in AI for autonomous cloud orchestration, cross-cloud data analytics, and standardization efforts to further streamline multi-cloud interoperability. This research offers valuable insights for cloud architects, enterprises, and service providers aiming to design scalable, secure, and efficient cloud infrastructures for the digital era.